SUPLEMENTASI DAUN TORBANGUN (COLEUS AMBOINICUS LOUR) UNTUK MENURUNKAN KELUHAN SINDROM PRAMENSTRUASI PADA REMAJA PUTRI (SUPPLEMENTATION OF TORBANGUN LEAVES [COLEUS AMBOINICUS LOUR] IN REDUCING THE COMPLAINST OF PRE-MENSTRUAL SYNDROME [PMS] AMONG TEENAGE G - Devi, Mazarina; Syarief, Hidayat; Damanik, Rizal; Sulaeman, Ahmad; Setiawan, Budi; Dewi, Rousmala (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2013)
ABSTRACT Background: Torbangun leaves (Coleus ambonicus Lour) is one of type of species from Labiatae family which contains a lot of micronutrient and active element which have been examined as beneficial for human health and quality of life. The plants containing iridoid and flavonoid as well as phytochemical which deal with reproduction hormone is applicable to traditional medication toward PMS cases. Methods: The present study was aimed to assess the efficacy of CAL leaves in the management of PMS. An experimental clinical trial was conducted in 35 teenagers with PMS. Three intervention groups were defined: CAL leaves; commercial preparation; and placebo. Participants were followed-up individually for 1 month. Result: The results showed average menarche occurred around age 13 years, with menstruation lasting 5 days. During each successive treatment cycle, participants experienced a lower pain intensity score. Chi Square test, after adjusting each cycle for baseline pain, treatment compliance and other variables, showed that the group receiving CAL extract had significantly reduced pain intensity (p<0.05) compared with commercial preparation and placebo. Conclusion: The torbangun leaves supplement can be used as treatment to relief symptoms of the premenstrual syndrome. [Penel Gizi Makan 2010, 33(2):180-194] Keywords: Torbangun leaves (Coleus amboinicus Lour), pre-menstrual syndrome (PMS), teenage girls